2014
DOI: 10.1371/journal.pone.0089772
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary (Rosmarinus officinalis) Extract Modulates CHOP/GADD153 to Promote Androgen Receptor Degradation and Decreases Xenograft Tumor Growth

Abstract: The Mediterranean diet has long been attributed to preventing or delaying the onset of cardiovascular disease, diabetes and various solid organ cancers. In this particular study, a rosemary extract standardized to carnosic acid was evaluated for its potential in disrupting the endoplasmic reticulum machinery to decrease the viability of prostate cancer cells and promote degradation of the androgen receptor. Two human prostate cancer cell lines, 22Rv1 and LNCaP, and prostate epithelial cells procured from two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 29 publications
4
51
0
Order By: Relevance
“…In support of the activation of the reactive mode of UPR by CA treatment, several published studies suggest that CA induces ER stress in various cell types (21,24,29,49). Also, it has been shown that the UPR contributes signals to cell death pathways in CA-treated cells as consequence of severe or unresolved ER stress that determine cell fate (21,24), a mechanism that does not occur in the anticipatory UPR (48). It has been suggested that this effect was caused by a redox imbalance because of the elevation of intracellular reactive oxygen species (ROS) levels, a condition that is generally believed to alter ER homeostasis (24).…”
Section: ϫ132mentioning
confidence: 93%
See 2 more Smart Citations
“…In support of the activation of the reactive mode of UPR by CA treatment, several published studies suggest that CA induces ER stress in various cell types (21,24,29,49). Also, it has been shown that the UPR contributes signals to cell death pathways in CA-treated cells as consequence of severe or unresolved ER stress that determine cell fate (21,24), a mechanism that does not occur in the anticipatory UPR (48). It has been suggested that this effect was caused by a redox imbalance because of the elevation of intracellular reactive oxygen species (ROS) levels, a condition that is generally believed to alter ER homeostasis (24).…”
Section: ϫ132mentioning
confidence: 93%
“…In our study, such UPR signaling pattern does not seem compatible with the observed elevated levels of the eleven ATF4-regulated proteins in CA-treated cells. In support of the activation of the reactive mode of UPR by CA treatment, several published studies suggest that CA induces ER stress in various cell types (21,24,29,49). Also, it has been shown that the UPR contributes signals to cell death pathways in CA-treated cells as consequence of severe or unresolved ER stress that determine cell fate (21,24), a mechanism that does not occur in the anticipatory UPR (48).…”
Section: ϫ132mentioning
confidence: 96%
See 1 more Smart Citation
“…19 From the oral cavity, P. aeruginosa can be disseminated systemically and cause respiratory infection, particularly in hospitalized and immunosuppressed patients. 20 The action of different types of R. officinalis L. extracts was reported on some tumor cell lines such as the ovarian cancer (SK-OV-3 and HO-8910), hepatocellular carcinoma (Bel-7402), 21 colorectal cancer (SW620 and DLD-1), pancreas cancer (MIA-PaCa-2 and PANC-1), 22 prostate cancer (LNCaP and 22Rv1), 23 colorectal adenocarcinoma (LoVo), hepatocarcinoma (HepG2). On the target lineages in this study, MCF-7 24 and HeLa, 25 the action of R. officinalis L has also been reported; however, in our study, we used three different cell viability tests and glycolic extract.…”
Section: Introductionmentioning
confidence: 99%
“…Anticarcinogenic effects of many plants derivatives, by inhibiting cancer cell proliferation in vitro, were assessed in many scientific reports (Galasso et al, 2014;Petiwala et al, 2014;Mastron et al, 2015).…”
Section: Introductionmentioning
confidence: 99%